Blockchain-based system for storage utilisation and secure sharing of EHR data. Issue 3 (3rd October 2022) - Chandran, Anjana S.
The vast storage volume is one of the key roadblocks to BlockChain (BC) development. Thus, finding a means to optimise the storing mechanism is critical. So, this research developed a useful BC-centred approach for data preservation and secured sharing in Electronic Health Records (EHRs). The Data Deduplication (DD) idea is used to utilise memory. The uploaded file's Hash Code (HC) is generated using the Stribog hashing algorithm. DD is tested based on this technique to avoid storing duplicate copies of data. To ensure security, the system uses Modified Ciphertext-Policy Attribute-Based Encryption (MCP-ABE) to collect data in an encrypted format in the distributed cloud. The Distributed Cloud Servers (DCS) are chosen using the Weight and Exhaustiveness-based Harris Hawks Optimisation (WEH²O). Finally, the data is safely stored on a BC-based cloud that also provides security. Based on the experimental results, the proposed work performed better than the existing data transmission methods.